Fractalkine/CX3CL1 and macrophage inflammatory protein-1?/CCL4 activity in the rat ovary with induced ovarian hyperstimulation? - Akverdi, Gulcan; Pala, Sehmus; Atilgan, Remzi; Kuloglu, Tuncay; Hancer, Serhat; Ilhan, Nevin (Galenos Publ House, 2024)
Objective: Fractalkine (CX3CL1) and macrophage inflammatory protein-1 beta (MIP-1 beta)/CCL4 play a role in chemotactic activity, immune response, and inflammatory response. We aimed to investigate the effects of fractalkine and MIP-1 beta in the development of ovarian hyperstimulation syndrome (OHSS) by considering the inflammatory response during ovulation. Materials and Methods: Two equal groups of 20 immature female rats were created. Given that one of the rats in the group died, the control group was made up of 9 rats. Group 1 (G1) (n=9): Control group; G2 (n=10): OHSS group. Rats in the G2 group were administered 10 IU FSH for 4 days and 30 IU human chorionic gonadotropin on the fifth day. At 34 days old, all rats were sacrificed, and blood and ovarian tissue samples were collected to measure CX3CL1, CX3CL1R, MIP-1 beta, tumor necrosis factor-alpha (TNF-alpha), interleukin (IL-8), hypoxia-inducible factor (HIF-1 alpha), and interferon-gamma (IFN-gamma) levels. Immunohistochemical scoring was performed for CX3CL1 and CX3CL1R in other ovarian tissue. Results: Rat and ovary weights and serum CX3CL1, CX3CLR1, HIF-1 alpha, MIP-1 beta, TNF-alpha, IFN-gamma and IL-8 levels were significantly higher in G2 than in G1. Tissue IL-8, TNF-alpha, CX3CL1, CX3CLR1, MIP-1 beta levels and CX3CL1 and CX3CLR1 immunoreactivity scores were significantly higher in G2 than in G1. Conclusion: CX3CL1 and MIP-1 beta contribute to the pathophysiology of OHSS by playing a role in the development of inflammation.
İndüklenmiş ovaryan hiperstimülasyonlu olan sıçan overinde fraktalkin/CX3CL1 ve makrofaj enflamatuvar protein-1?/CCL4 aktivitesinin araştırılması
Keywords: OHSS; fractalkine/CX3CL1; CCL4/MIP-1 beta; rat